THE DYNAMIC RELATIONSHIP BETWEEN STOCK PRICES AND EXCHANGE RATES: EVIDENCE FROM INDONESIA (Case Study In Indonesian Stock Exchange from July 2001 - April 2008) - Nugroho, Leonardus Jayadi; Mawardi, Wisnu (JURNAL BISNIS STRATEGI, 2008)
The aim of this study is to examine the dynamic relationship between stock prices and exchange rates by using high-frequency data of exchange rates and composite index of stock prices (IHSG) of Indonesia for the period July 2001 to April 2008. Applying Johansen's cointegration analysis, the study identifies a long-run relationship between stock price and exchange rate. Furthermore, using Granger Causality Test, this study proceed to test for short-run causal relationships between stock prices and exchanges rates and found one unidirectional relationship from stock prices to exchange rates. Analysis of vector error correction (VEG) model reveals that the Rupiah exchange rate is affected by both the past exchange rate and the stock price (ceteris paribus). On the other hand, the stock price is apparently only affected by its past movement. These results are supported by innovative accounting (impulse response function and variance decomposition). The conclusion can be drawn in this study is the stock price seems to be a leading indicator of the relationship between stock price and exchange rate, which is following the Portfolio Balance Approach. The results have implications for investors, policy makers and researchers.